(untitled) (Kronika Bydgoska, 2020)
The article presents a possibility of using mortgage and land files and registers dating from the 18th and 19th centuries, showing particularly their suitability in research in the context of the history of Bydgoszcz as well as urban and spatial development of the city. This article features a brief history of mortgage records as registers collecting inform ation on legal status, ow nership and m ortgage of specific real estate, as w ell as archival description of files. In an analysis of exam ples of materials, the author indicated places, in which one can easily find descriptions of real estates, tenement houses and buildings, their ow ners and information about transactions conducted by them. Mortgage and land registers, in addition to the area of research on development of the city, have valuable files since their contain documents searched by genealogists, including copies of vital records, property division records, successions, etc. The article encourages m ore extensive use of files contained in the Bydgoszcz Archives of Mortgage Registers, also by conservator-restorers, art historians, and finally ordinary users who look for information needed in property and inheritance issues.